2022
DOI: 10.1371/journal.pone.0277288
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 vaccination on the menstrual pattern and mental health of the medical students: A mixed-methods study from a low and middle-income country

Abstract: Objective To assess the effect of COVID-19 vaccination on menstrual patterns and mental health of medical students and to explore the students’ perspective regarding this effect. Materials and methods This mixed-method study was conducted on the medical and dental students of the private and public sector institutions of Peshawar from September 2021 to March 2022. A Menstrual symptom questionnaire (MSQ) and hospital anxiety and depression scale (HADS) were used. This was followed by qualitative interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to our data, 86.63% of participants had no change in their menstrual pain and16.53% of participants' bleeding rate was more than before as respects a study in Saudi Arabia of 673 women concluded that the COVID-19 vaccination was associated with a slight change that led to more painful periods and increased bleeding [17]. Also, a study in Pakistan on 953 medical students showed that 41.2% of students had experienced dysmenorrhea, and 58.8% had problems with the frequency and flow of menstruation [18]. Perhaps the reason for the difference in the rate of menstrual pain in these studies is the different types of vaccines received.…”
Section: Discussionmentioning
confidence: 95%
“…According to our data, 86.63% of participants had no change in their menstrual pain and16.53% of participants' bleeding rate was more than before as respects a study in Saudi Arabia of 673 women concluded that the COVID-19 vaccination was associated with a slight change that led to more painful periods and increased bleeding [17]. Also, a study in Pakistan on 953 medical students showed that 41.2% of students had experienced dysmenorrhea, and 58.8% had problems with the frequency and flow of menstruation [18]. Perhaps the reason for the difference in the rate of menstrual pain in these studies is the different types of vaccines received.…”
Section: Discussionmentioning
confidence: 95%
“…We also note contraceptives are not the only drug, device, or biologic to impact the menstrual cycle, yet such data are not routinely collected during clinical trials or during standard toxicology and pharmacodynamics studies, as other organ functions and vital signs are. The lack of these data was recently highlighted with the initial introduction of COVID vaccinations when vaccinated people who could or did menstruate experienced unanticipated bleeding changes [3842]. We hope our work can be a guide and an invitation to develop recommendations for if, when, and how to measures changes to the menstrual cycle in more types of clinical trials and related research.…”
Section: Discussionmentioning
confidence: 97%
“…In a smaller Saudi-Arabian web-based survey on side-effects after COVID-19 vaccination Menstrual disturbances were reported in this open text field, and only a small proportion of the respondents reported abnormal menstrual cycle (delaying/increase hemorrhages or pain): 0.98% of Pfizer BioNTech and 0.68% (7/1028) of ChAdOx1 vaccinees [ 9 ]. Menstrual irregularities after both the first and second doses of the vaccine were found to self-resolve in approximately half the cases within two months [ 10 , 11 ]. Issakov et al reported the most generally described menstrual disturbance was bleeding [ 12 ] but our results shown latency or premature menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the six vaccine types in 6 Arabic countries, a higher percentage of menstrual irregularity was observed in Johnson & Johnson, followed by Sinopharm, Moderna, and AstraZeneca. Similarly, Johnson & Johnson was associated with a higher percentage of heavy bleeding with coagulations, followed by Pfizer, Sinopharm, AstraZeneca, and Moderna [ 11 ]. In our study latency of menstruation is more than other disturbances, also some of precipitants suffered from more than complication such as latency plus heavy bleeding or premature and spot bleeding together.…”
Section: Discussionmentioning
confidence: 99%